Peptide/protein separation with cationic polymer brush nanosponges for MALDI-MS analysis - Mitrovic, Bojan (Langmuir : the ACS journal of surfaces and colloids, 2013)
A cationic polymer nanobrush was synthesized, attached to a MALDI target, and used for the fractionation of peptides and proteins based on their pI, prior to analysis by MALDI-MS. The cationic polymer nanobrush was synthesized on a gold substrate by AIBN photoinitiated polymerization, using a 70:30 ratio of 2-aminoethyl methacrylate hydrochloride (AEMA):N-isopropylacrylamide (NIPAAM). This brush showed selectivity for adsorption of acidic peptides and proteins and allowed fractionation of simple two-component mixtures to be completed in less than 10 min. The brush-adsorbed biomolecules were recovered by treating the nanobrush with ammonium hydroxide, which effectively collapsed the brush, thereby releasing the trapped compounds for MALDI MS analysis. These results demonstrate that nanobrush can serve as a convenient platform for rapid fractionation of biomolecules prior to analysis by MALDI-MS